CGIAR climate security supports the global effort for information integrity about climate change - Carneiro, Bia; Tucci, Giulia; Taiwo, Ibukun (2025)
This year, CGIAR Climate Security has deepened the Alliance of Bioversity International and CIAT’s commitment to using its climate science for good by joining the Global Initiative for Information Integrity about Climate Change.